Photographs of what is not in NYC. The notion of ruin in visual representations of New York City during the Covid-19 pandemic - Chueca, José Gabriel (2020)
In this article, I propose a relationship between the modern notion of ruin and a set of specific photographic representations of New York City during the first two weeks  of impact from the Covid-19 pandemic. The body of images  analyzed is composed of a group of pictures published on  the front page of The New York Times during March 2020.  This set of pictures has been chosen as representative of a  photographic genre that I call «pictures of what is not there», characterized by the depiction of city landmarks emptied of people as a direct consequence of the pandemic. To  analyze the common aspects of the aforementioned genre  and the depictions of ruins popularized in Europe during  the 17th and 18th centuries —the early modern period— I  resort to Aby Warburg’s notion of «visual survivals'', identifying anachronistic cultural recurrences that are key to our  reflection upon the present moment.